Analysis, control and experimental verification of a single‐phase capacitive‐coupling grid‐connected inverter. Issue 5 (1st May 2015) - Dai, Ning‐Yi; Zhang, Wen‐Chen; Wong, Man‐Chung; Guerrero, Josep M.; Lam, Chi‐Seng
Abstract : This study proposes a capacitive‐coupling grid‐connected inverter (CGCI), which consists of a full‐bridge single‐phase inverter coupled to a power grid via one capacitor in series with an inductor. The fundamental‐frequency impedance of the coupling branch is capacitive. In contrast with the conventional inductive‐coupling grid‐connected inverter (IGCI), this structure provides an alternative interface for use between a low‐voltage DC microgrid and an AC grid. A comparison between the CGCI and the IGCI is performed. It is concluded that the CGCI is able to transfer active power and provide lagging reactive power at an operational voltage much lower than that of the IGCI. This reduces the system's initial cost and operational losses, as well as the energy stored in the DC‐link capacitor. The CGCI has been analysed and a DC voltage selection method is proposed. Using this method, the DC‐link voltage of the CGCI remains at approximately of 50% of the peak grid voltage. In addition, a P ‐unit current controller is proposed for use with the CGCI, as a proportional–integral controller is not suitable. Finally, simulation and experiments show the effectiveness of the proposed approach.